Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

La contribution des femmes à l’histoire de la musique au Québec - Lefebvre, Marie-Thérèse (New Sound, 1998)
Lors d'un colloque international sur les femmes et la création musicale organise par I'Unesco en mars 1996, Mme Zaimont et Mme Ostleitner des Etats-Unis et de I'Autriche, ont démontre dans leur conférence respective á quel point la vie musicale des pays qu'elles représente est encore puissamment dominée par les forces conservatrices et traditionnelles I'Autriche plie sous le poids d'un héritage musical ancestral alors que les Etats-Unis (et jusqu'a un certain point le Canada anglophone) vit actuellement au rythme des tendances politiques de droite. Plusieurs des acquis du mouvement féministe sont actuellement remis en question dans les milieux décisionnels et on ne peut que s'inquiéter de I' impact que pourraient avoir ces mouvements conservateurs sur la création musicale des femmes de ce pays. Mais dans ce même colloque, nous avons également pu entendre les propos de représentantes d'autres pays, je pense ici a la Corée au Japon, a la Bolivie, a I'Uruguay ou les femmes prennent une place de plus en plus importante dans le discours musical et dans la production artistique. De son cote, Le Québec, peut-être a cause de sa situation linguistique et culturelle minoritaire, a développe au cours de son histoire une vitalité artistique enviable et a été a I'avant-garde dans plusieurs domaines dont la création musicale. Le réseau de solidarité que les femmes ont bâti dans le milieu musical depuis quelques années et la place que les compositrices occupent aujourd'hui témoignent de cette vitalité.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; discipline; femmes* artistes; femmes* compositrices; histoire; histoire des femmes*; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail